2017
DOI: 10.1080/15548627.2016.1252889
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of ERMES components by the E3 ligase Rsp5 is involved in mitophagy

Abstract: Mitochondria are dynamic organelles that undergo permanent fission and fusion events. These processes play an essential role in maintaining normal cellular function. In the yeast Saccharomyces cerevisiae, the endoplasmic reticulum-mitochondrial encounter structure (ERMES) is a marker of sites of mitochondrial division, but it is also involved in a plethora of other mitochondrial functions. However, it remains unclear how these different functions are regulated. We show here that Mdm34 and Mdm12, 2 components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 74 publications
2
35
0
1
Order By: Relevance
“…The latest studies have shown that mitochondria are targets of polyubiquitin [40, 41]. Studies have also shown that ubiquitinated PHB is present in mammalian sperm mitochondria, suggesting that this protein may mediate the ubiquitination of spermatozoa mitochondria [11].…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies have shown that mitochondria are targets of polyubiquitin [40, 41]. Studies have also shown that ubiquitinated PHB is present in mammalian sperm mitochondria, suggesting that this protein may mediate the ubiquitination of spermatozoa mitochondria [11].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mitochondria anchoring Gem1, a Ca 2+ -binding small GTPase, directly associates with the ERMES complex and regulates its size and number (14)(15)(16). ERMES components are also regulated by Rsp5 E3 ubiquitin ligase, and ubiquitination is required for efficient mitophagy (17).…”
mentioning
confidence: 99%
“…Furthermore, the ER membrane protein complex (EMC) comprising conserved Emc1-Emc6 proteins performs a comparable role in lipid transfer from the ER to mitochondria by mediating tethering between these organelles (26). In addition to lipid trafficking, other functions of the ERMES complex have been reported, including mitochondrial protein assembly (27) and import (28), maintenance of mitochondrial DNA (15,29,30), mitochondria inheritance (31), and mitophagy (17,(32)(33)(34).…”
mentioning
confidence: 99%
“…It is essential for viability that dysfunctional mitochondria are removed, which occurs via mitophagy 40 . Efficient mitophagy requires ubiquitination of the ERMES components Mdm34 and Mdm12 163 . Moreover, ERMES colocalizes with the site of mitophagosome generation and the ER was proposed to deliver the necessary lipids for membrane engulfment of the mitochondrion 164 165 .…”
Section: Ph Control Stress Tolerance and Longevitymentioning
confidence: 99%